(untitled) (Hekima Review, 2011)
N’teba Mbengi Anicet’s Book is an adaptation of his doctorate thesis defended at the Pontifi cal Gregorian University. The research was on the Church History. N’teba is a Jesuit from Democratic Republic of Congo (DRC). The book studies the mission entrusted to the Jesuits from 1892 in one of the largest regions of DRC. This mission was designated under the title of Kwango’ Mission and included three regions: The Bas Congo (south West of DRC), The Kwilu and the Kwango, regions situated in the actual province of Bandundu (central West of DRC). The author has focused his study on the period between 1901 and 1954 and tries to enlighten the contribution of the Jesuits to the transformation of that region, especially in the Kwilu.